2018
DOI: 10.1016/j.physbeh.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Differing structural properties of foods affect the development of mandibular control and muscle coordination in infants and young children

Abstract: The development of chewing is an essential motor skill that is continually refined throughout early childhood. From a motor control perspective, the advancement of textures is dependent upon the fit between a child's oral anatomic and motor system and food properties. The purpose of this exploratory study is to identify age-related changes in chewing motor coordination and control and to determine if these changes are associated with the differing structural properties of solid foods, as well as to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 56 publications
(95 reference statements)
2
21
0
2
Order By: Relevance
“…They are in the third quartile similarly. Moreover, right and left superoinferior localization are at 53.27% and 52.43% respectively which are also at the third quartile [9]. In addition, Oguz and Bozkir [11] .84 mm and there are some statistically significant differences between left and right sides in AB-PB, MF-IB, MN-IB parameters which is differed from previous studies showed no statistically significant difference in these parameters.…”
Section: Discussionmentioning
confidence: 71%
“…They are in the third quartile similarly. Moreover, right and left superoinferior localization are at 53.27% and 52.43% respectively which are also at the third quartile [9]. In addition, Oguz and Bozkir [11] .84 mm and there are some statistically significant differences between left and right sides in AB-PB, MF-IB, MN-IB parameters which is differed from previous studies showed no statistically significant difference in these parameters.…”
Section: Discussionmentioning
confidence: 71%
“…This food related masticatory behavior was previously described in adults using food and nonfood samples of increasing hardness (Fontijn‐Tekamp, van der Bilt, Abbink, & Bosman, ; Jalabert‐Malbos et al, ; Shiau, Peng, & Hsu, ; Woda, Foster, et al, ). Moreover, studies performed on babies and infants suggested that the capacity to adapt to different foods may appear as soon as food diversification begins (Gisel, ; Simione et al, ; Wilson et al, ). However, the diversity in foods (semi‐liquid/solid…) and procedures used in mastication studies in children avoided comparisons and made it difficult to draw conclusions, especially because children may use different orofacial praxes to deal with the task at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient mastication helps with the development of the brain, improves gustation and pronunciation, helps prevent obesity and dental caries, facilitates swallowing, and acts to regulate digestion [1,2]. These benefits of mastication are very important for the physical growth and development of children and adolescents [3,4]. On the other hand, recent studies have also demonstrated that mastication has an intrinsic relationship to dementia and cognitive function in the elderly [5,6].…”
Section: Introductionmentioning
confidence: 99%